Konsep Rooftop Greenhouse Terintegrasi Smart Rain Water Harvesting Irrigation Sebagai Solusi Pertanian Berkelanjutan di Perkotaan (International Forum of Researchers and Lecturers, 2023)
The conversion of agricultural land in large urban areas like Jakarta has the potential to threaten food security, therefore a breakthrough in the form of an efficient urban farming model is needed. This research aims to formulate a conceptual model of an automatic irrigation system integrated with a greenhouse or greenhouse that utilizes rain water harvesting as a solution for changing the function of agricultural land in urban areas. The research method uses a literature study by examining references from 12 scientific journals and 3 textbooks related to the topic of agricultural land conversion, agricultural irrigation systems, rainwater harvesting, and the greenhouse concept. The results of the conceptual model formulation show that rainwater collected in an underground reservoir can be utilized optimally and sustainably through an automatic irrigation system to supply the water needs of agricultural land in a greenhouse on the roof of a building. This model has the potential to be a solution for changing the function of agricultural land in urban areas while supporting food security. Further studies are needed regarding specific soil moisture for various types of plants as well as direct model testing.